Male versus female career ambassadors: is the US Foreign Service still biased? - Calin, Costel; Buterbaugh, Kevin (Foreign Policy Analysis, 2019)
This paper examines the appointment of male versus female career diplomats to ambassadorial posts. We assess the role played by ambassadors' individual characteristics, including education, marital status, and number of children, and host countries' characteristics, such as quality of life and regime type, in determining if a male or female is appointed to ambassadorial positions to represent the United States in foreign countries. The time frame of this study is the entire presidencies of Bill Clinton and George W. Bush (1993-2008), during which 603 career diplomats were appointed as ambassadors. The study provides empirical evidence that there remain significant differences between women and men serving as ambassadors. Female ambassadors are more likely to be single and have no children and are less likely to be Ivy League graduates than male ambassadors. Furthermore, they are more likely to be appointed to countries with lower quality of life and better human rights records. Finally, time plays a role in the likelihood of a woman being appointed as ambassador.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481423500004, lens.org/085-024-674-912-250 tex.address: [object Object] tex.affiliation: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: dept.psc; peer-reviewed